Data analysis methodologies for hydrodynamic experiments in waves (Journal of Naval Architecture and Marine Engineering, 2016)
This paper presents the methodologies developed in order to quality control and analyze the data acquired in hydrodynamic seakeeping experiments of physical models in waves. In such experiments, the data file consists of wave elevations and directions, loads, motions, velocities and accelerations of one or multiple bodies. Additionally, mooring, slamming, sea-fastening, fender and other vessel specific load data may be acquired, which requires special analysis technique. Data products of such experiments are primarily consist of the basic statistics of each of the acquired data channels selected segments. Various wave statistics are produced to estimate the significant and other percentile of peaks/troughs/heights of each relevant data signal. This is done for the wave segment using zero crossing analysis. The response amplitude operator analysis is done through spectral analysis. Weibull analysis is done to estimate the maximum and minimum of an occurrence in a projected time. Analysis routines are written to incorporate each of these analysis techniques to produce results both in tabular and graphical formats. Analysis technique for decay experiments in multiple directions of motion, which are integral parts of any sea-keeping experiments, is also presented. Examples of all such analysis are provided where appropriate.